Aragonite saturation state and dynamic mechanism in the southern Yellow Sea, China. Issue 1 (15th August 2016) - Xu, Xuemei; Zang, Kunpeng; Huo, Cheng; Zheng, Nan; Zhao, Huade; Wang, Juying; Sun, Bing
Abstract: Based upon surveys conducted in November 2012 and June 2013, the distribution and dynamics of aragonite saturation state (Ωarag ) were investigated in the southern Yellow Sea (SYS) of China. In summer, surface water Ωarag ranged from 2.1–3.8 and enhanced biological production fueled by Changjiang River freshwater input increased Ωarag to 3.8 in the southern SYS. However, subsurface water Ωarag was < 2.0 in the central SYS. During autumn, surface water Ωarag was 2.0–2.9, lower than that in summer due to ventilation between surface and low Ωarag (1.0–1.4) subsurface waters in the central SYS. Community respiration and/or aerobic remineralization dominated low Ωarag in subsurface waters, while water stratification influenced the level and scale of acidity accumulation. By the end of this century, waters with Ωarag > 2.0 could disappear from the SYS with increasing atmospheric CO2, while bottom waters Ωarag may become undersaturated due to the impact of eutrophication. Highlights: Distribution and dynamics of Ωarag were investigated in the southern Yellow Sea of China. Enhanced biological production increased surface water Ωarag to 3.8 in the southern SYS in summer. Community respiration and/or aerobic remineralization dominated low Ωarag in subsurface waters. Water stratification influenced the level and scale of acidity accumulation. Waters with Ωarag > 2.0 could disappear from the SYS by the end of this century.